Odpowiedzi

2010-04-08T17:02:13+02:00
A)3/x-2=4/2x+1 /*2x
6-4x=4+2x
-4x-2x=4-6
-8x=-2
x=1/4

b)2/3=3x+2/2x-2 /6x
4x=18x+6-12x
4x-18x+12x=6
-2x=6
x=-3

c)6x-1/x+1=2,3/1,2
6x-1/x+1=23/12 /*12x
72-12+12x=23x
12x-23x=-72+12
-11x=-60
x=60/11

d)-x/3x-1=2x/1-6x /3x
-x-3x=6x-18x
-x-3x+18x-6x=0
8x=0
x=0


2010-04-08T17:15:58+02:00
A)
3/x-4/2x=3
6/2x-4/2x=3
x=3;)
b)
2/3+2=3x+x
8/3=4x
x=2/3
d)
-x/3x=-1/3
a więc;
-1/3-1=2x/1-6x
-2/3=2x/1-6x mnożymy przez 1-6x
2(1-6x)÷3=2x mnożymy przez 3
2-12x=6x
2=18x
x=9;))